"Natural" relief of pregnancy-related symptoms and neonatal outcomes: above all do no harm. (4th November 2015) - Trabace, Luigia; Tucci, Paolo; Ciuffreda, Lucia; Matteo, Maria; Fortunato, Francesca; Campolongo, Patrizia; Trezza, Viviana; Cuomo, Vincenzo
Abstract: Ethnopharmacological relevance: In the South of Italy the use of herbal remedies to alleviate pregnancy-related symptoms is very common. Objectives: To investigate the proportion, prevalence of use, attitude and knowledge base in a sample of Italian pregnant women in the South of Italy. To explore the possible influence and risks of herbal consumption on pregnancy and neonatal outcomes. Methods: A retrospective observational study was conducted during the study period November 2010–September 2013. Six hundred and thirty expectant mothers were interviewed within three days after childbirth in a public Hospital in the South of Italy. Results: Due to a lack of data, a total of six hundred interviews were considered. Four hundred and eighty six women (81%) reported to have constantly used at least one herbal product throughout the pregnancy period. The study enrolled mostly women between 31 and 40 years of age, with a middle-high level of education, married and employed. The most commonly used herbal products, taken by oral route and for the entire period of pregnancy, were chamomile, fennel, propolis, cranberry, lemon balm, ginger, valerian and mallow. The most relevant source of information for the majority of participants was the doctor (95%), and most of the women (72%) informed their doctors about their use of herbal remedies. Conclusions: The regular chamomile consumption resulted in a higher risk of pre-term delivery, lower birth weight and lower length of the newborn. Also a regular use of fennel resulted in a shorter gestational age. Finally, ginger intake resulted in a shorter gestational age and in a smaller circumference of the newborn's skull. Graphical abstract: